Public perception of ex quarry land utilization (quarry) as bussiness place of floating net cages culture (fnc) in tanjung rambutan village kampar district kampar regency Riau province - Jalisman '; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conduted on 27th May to 3th June 2013 in Tanjung Rambutan Village, district of Kampar that located in regent of Kampar Riau Province. This research was determined purposively with survey method. The respondents was taken by simple random sampling.The purpose of this study was to describe public characteristics are age, education, income and number of dependents. Analyzed public‟s perception of ex quarry land utlization and know how much the relationship public perception characteristics Tanjung Rambutan village between the ex quarry land utilization (Quarri) used the Spearman Rank Correlation Coefficienttest.The results of this study indicated that the public perception of the ex quarry land utilization as a whole was in the category of "Good", with a score of 1496, which is in the range 1283-1795. Internal factor did not have significant affect to respondent‟s percepcion in Tanjung Rambutan village (age, education, occupation and income). While number of dependents had significant correlanced to respondents percepcion about quarri land utilization in Tanjung Rambutan.Keyword: Perception, Tanjung Rambutan Village, Ex quarry land (Quarri)